Identification of a persistent primitive trigeminal artery following the transposition technique for trigeminal neuralgia: A case report - Kato, Naoki (Pulsus Group Inc, 2011)
A patient who presented with trigeminal neuralgia associated with a persistent primitive trigeminal artery (PPTA) is presented. A 62-year-old woman suffering from right orbital pain was admitted to the hospital. Medical treatment for three months was ineffective, and her neuralgia had deteriorated and gradually spread in the maxillary division. Magnetic resonance imaging demonstrated the flow void signal attached to the right trigeminal nerve. Thus, microvascular decompression was performed. The superior cerebellar artery was the responsible artery, and it was transposed to decompress the trigeminal nerve. After this manoeuvre, an artery was identified running parallel to the trigeminal nerve toward Meckel’s cave. The artery, which turned out to be a PPTA, communicated with the basilar artery. The PPTA was carefully observed, and it was found not to be the artery causing the neuralgia because it did not compress the nerve at surgical observation. No additional procedure between the PPTA and the trigeminal nerve was performed. The patient’s symptom improved dramatically following surgery, and her postoperative course was uneventful. Postoperative three-dimensional computed tomography showed the PPTA. The findings in the present case suggest that transposition of the responsible artery effectively decompresses the root entry zone and assists in determining whether the PPTA is affecting the trigeminal nerve.